SINTESIS SENYAWA ANALOG PGV-0 DENGAN KATALIS ASAM SULFAT PEKAT SERTA UJI ANTIPROLIFERATIF TERHADAP SEL HeLa - , Hari Widada ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Prevention and treatment efforts of cancer is becoming increasingly crucial given the type and level of the higher incidence. The research of anticancer drug compounds is still being conducted and has been related to drugs that have a high selectivity and specificity towards cancer cells. Pentagamavunon-0 (PGV-0) as a synthetic compound that was developed from curcumin as a lead compounds have been studied as an inhibitor of cyclooxygenase (COX) activity with no specific measurement (Nurrochmad, 1999), cytotoxicity against myeloma cells (Nurrochmad, 2001) and test the cytotoxicity against Raji cells , HeLa cells and myeloma cells are found PGV-0 has potential as an anticancer drug better than curcumin (Daâi, 2003). Research was conducted to determine the potential antiproliferative several compounds derived PGV-0 on HeLa cells obtained by synthesis using concentrated sulfuric acid catalyst. Synthesis of PGV-0 compounds and its analogues with concentrated sulfuric acid catalyst is done in the absence of solvent, the solvent methanol and the solvent 2- Butanol with refluxed generate the amount of different yield. Purification of compounds synthesized carried by washing with hot water (90 Â° C) and recrystallization with a suitable solvent. Purity analysis conducted with melting point test and Thin Layer Chromatography (TLC). The characterization of the synthesized compounds by the method of structure elucidation carried using a IR spectrophotometer, 1H-NMR spectrometer and a mass spectrometer. Cytotoxic test was conducted by MTT test. And the data were analyzed by probit analysis and doubling time analysis. Cytotoxic assay committed against HeLa cells to acquire data in the form of potential cytotoxic IC50 values. PGV-0 compound and its analogs are cytotoxic against HeLa cells with IC50 values respectively as follows: 0,055 mM (PGV-0), 0,656 mM (MT-OH), 5,376 mM (MT-Cl), 5,723 mM [MT-N(CH3)2]. Analysis doubling time is only committed against compound PGV-0